2010
DOI: 10.1007/s10772-010-9073-1
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of speech enhancement using wavelet filtering method

Abstract: This paper investigates the utilization of wavelet filters via multistage convolution by Reverse Biorthogonal Wavelets (RBW) in high and low pass band frequency parts of speech signal. Speech signal is decomposed into two pass bands of frequency; high and low, and then the noise is removed in each band individually in different stages via wavelet filters. This approach provides better outcomes because it does not cut the speech information, which occurs when utilizing conventional thresholding. We tested the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The Yule-Walker parametric method calculates the AR parameters through the biased estimation of the autocorrelation function given by Equation ( The wavelet threshold denoising method is applied by employing a multilevel 1D wavelet analysis by Daubechies family [49,50]. The wavelet decomposition structure of the signal is extracted.…”
Section: Approach For Delamination Detection and Diagnosis In Wtbmentioning
confidence: 99%
“…The Yule-Walker parametric method calculates the AR parameters through the biased estimation of the autocorrelation function given by Equation ( The wavelet threshold denoising method is applied by employing a multilevel 1D wavelet analysis by Daubechies family [49,50]. The wavelet decomposition structure of the signal is extracted.…”
Section: Approach For Delamination Detection and Diagnosis In Wtbmentioning
confidence: 99%
“…Also, by taking the inner product between the original signal and the wavelet functions, the DWT coefficients can be produced. Given that wavelet functions are simply translated and dilated versions of each other, a simpler algorithm, known as Mallat's pyramid tree algorithm, has been proposed ( Figure 2) [45][46][47].…”
Section: Discrete Wavelet Transformmentioning
confidence: 99%
“…where W L (p, j) is the p-th scaling coefficient at the j-th stage, W H (p, j) is the p-th wavelet coefficient at the j-th stage, and h(n), g(n) are the dilation coefficients relating to the scaling and wavelet functions, respectively [47]. In the last decade, a tremendous increase in the applications of wavelets, in various scientific fields, has emerged [46].…”
Section: Discrete Wavelet Transformmentioning
confidence: 99%
See 1 more Smart Citation
“…Khaled Daqrouq et al [13] proposed a multistage convolution approach in which Reverse Biorthogonal Wavelets are used. The authors observed better quality improvements in the enhancement of the speech signal.…”
Section: Related Workmentioning
confidence: 99%